137 Evidence based ESMO-ESGO-ESTRO endometrial cancer guidelines: are adequate for planning adjuvant therapy?. (13th November 2020) - Fuso, L; Badellino, E; Laudani, M; Carapezzi, A; Parpinel, G; Petey, F; Barboni, M; Ribotta, M; Volpi, E; Ferrero, A; Zola, P
Abstract : Introduction: Endometrial cancer is the most common gynaecological cancer in developed countries. Since 2014 the ESMO-ESGO-ESTRO societies have made a great effort to outline guidelines: modulation of adjuvant therapy is even more important as advanced age and frequent co-morbidities may limit therapeutic success. It is therefore of overwhelming importance to avoid over/under-treatment. Methods: To verify the impact of treatment according to current European guidelines data over a 8 years period (01/2011 to 10/2018) were retrospectively collected in 3 Centres of the Piemonte and Valle d'Aosta Regional Cancer Network. Patients were classified according to ESMO risk class and the treatment carried out: if totally in accordance with the current guidelines, under or over-treated. Results: 723 patients were enrolled. As regards stage I endometrioid disease in accordance with the ESMO risk 237 were low risk, 94 intermediate, 132 High-intermediate and 42 high risk. Among these, they were treated in accordance with current guidelines respectively 97%, 79%, 46%, 31% of the patients with good results (98.6% censored). At the same time 3%, 21%, 14%, 33% were over-treated while 40% High-intermediate and 36% high risk undertreated. According to Cox regression survival analysis undertreatment gives a risk of death on overall survival of 9.3 (p=0.0001) compared to proper treatment but also overtreatment provide unfavourable effect OR=3.7 (p=0.05). At multivariate Cox analysis this upshot was maintained adjusting for age and ESMO risk (p=0.001). Conclusions: Patients treated in accordance with European guidelines have a good cure index, it is necessary to avoid over/under-treatment.